Analisis Dimensi Komitmen Organisasional yang Mempengaruhi Organizational Citizenship Behavior Karyawan PT KAI DAOP VI Yogyakarta - Suhartini, Yati (Universitas PGRI Yogyakarta, 2018)
The research was carried out to find the influence of three dimensions of organizational commitment, namely affective commitment, continuity commitment, and normative commitment, toward organizational citizenship behavior (OCB) of employees.The research was conducted respectively from seven stations in operation areas of PT Kereta Api Daop VI Yogyakarta.The subject of research are 55 employees Data was derived from a survey, collected by applying questionnaires, analized by using multiple linier regression,and assisted by the application of SPSS 21 program.Based on the result of data analysis, it is showed that the three dimensions of organizational commitment, namely affective commitment (X1), continuity commitment (X2), and normative commitment (X3) influence partially or simultaneously on organizational citizenship behavior (Y) of employees, thus partially or simultaneously supporting the 5 hypotheses. These were indicated by the value of regression coefficient and the significant level of each factor which are 0.250 and 0.042; 0.386 and 0.001; 0.481and 0,000, respectively. Likewise, the value of F amounting to 30.520 with the significance level of 0,000, whereas adjusted R2 counting to 0.621. Furthermore, normative commitment indicates as the most dominant dimension that influences on organizational citizenship behavior of employees.